PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP MINAT BELI KONSUMEN PT HIJRAH INSAN KARIMA BEKASI - Hafizh Igo Ramadhan; Arry Dwi Syahputra (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
The purpose to determine the effect of product quality and service quality on consumer buying interest PT. Hijrah Insan Karima Bekasi. The research method uses descriptive qualitative and quantitative analysis, the analytical model used is linear regression, both multiple and simple. The population in this study are consumers at PT. Hijrah Insan Karima Bekasi. The sampling technique of this study used simple random sampling. The sample as the object of research is respondents PT. Hijrah Insan Karima taken by chance. The result of Product quality and service quality have a positive and significant effect on consumer buying interest in PT. Hijrah Insan Karima Bekasi both simultaneous and partially.